Arts Archives: The use of sticks in performance training VHS - Serban, Andrei (Exeter Arts Documentation Unit, 1999)
Sticks have been used to train performers in different cultures and at different times - by the Peking Opera, Meyerhold, the Open Theatre and Peter Brook. This video is a record of varieties of stick work proposed by andrei Serban to a group of performers during a week-long training session in Leeds, UK. Serban, originally from Romania, worked with Brook in Paris, before going to New York to work with La Mama and currently at Columbia University. He has an international reputation as a director of theatre and opera.
Arts Archives
The fourth archive 1998-99 / 4
Keywords: الدراما; الدراما والمسرح